PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, SISTEM PENGENDALIAN INTERN, SISTEM AKUNTANSI KEUANGAN DAERAH, DAN SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI (Studi Pada SKPD Ka - Sanjaya, Aditya; Haryani, Eka; ', M. Rasuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Research aims to understand the influence of the application of government accounting standard, internal control system, regional financial accounting system, and human resources on the quality of local government financial statements with a commitment organization as moderation in Kampar Regency. This research using data primary. The samples serve as respondents taken by using the sampling method of proposive. Each population represented 3 respondents is the financial officer, treasurer, and staff treasurer. A questionnaire distributed to 96 respondents, and successfully reassembled with complete answers are obtained from 84 respondents. Analysis data using of multiple regression with the help of software SPSS Version 20.00. The result showed that government accounting system, internal control system, the accounting system are the significant effect on the quality of financial reports to the level of significance < 0,05. While the results of human resources is no effect to the quality of financial reports on the level of significance > 0,05. Regression analysis coefficient of determination (R2) of 0,976 or 97,6% which means that the independent variable in this study could affect the dependent variable, while the rest 2,4% is explained by other variables not included in this study.Keyword: standards, internal, financial, resources, and quality.